Allium Vegetables, Garlic Supplements, and Risk of Cancer: A Systematic Review and Meta-Analysis - Zhang, Qifan; Zhao, Qing; Shen, Yan; Zhao, Fuping; Zhu, Yan (Frontiers in Nutrition, 2022)
Purpose: Findings from laboratory studies have revealed that allium vegetables and garlic supplements may protect against cancer; however, related epidemiologic studies have produced inconsistent findings. Methods: We conducted a meta-analysis of published studies assessing the associations between allium vegetables, garlic supplements, and cancer risk. We pooled effect measures using fixed- or random-effects models to evaluate the highest and lowest consumption. A dose-response regression model was used to evaluate the relationship between allium vegetables, garlic supplements, and cancer risk. Results: In a pooled analysis of 22 studies with 25 reports on allium vegetables, no significant association was found between a high consumption of allium vegetables and cancer risk (relative risk [RR] = 0.97, 95% confidence interval [CI] 0.92–1.03) in a fixed-effects model. Similarly, garlic supplements were not found to be significantly associated with an increased risk of cancer (RR = 0.97, 95% CI 0.84–1.12) in a random-effects model involving a pooled analysis of 10 studies with 11 reports. Consumption of allium vegetables did not significantly correspond with cancer risk (P for nonlinearity = 0.958, P for linearity = 0.907). Conclusion: In this meta-analysis, we found no evidence that higher consumption of allium vegetables or garlic supplements reduced the risk of cancer; however, this finding requires further validation.